Perceptions and experiences of nurses about their performance in the COVID-19 pandemic - Elisabete Maria das Neves Borges; Cristina Maria Leite Queirós; Maria Rosário Fátima Sousa Pinheiro Vieira; Antónia Adília Ribeiro Teixeira (Universidade Federal do Ceará, 2021)
Objective: to describe the perception and experiences of nurses about their performance during the COVID-19 pandemic. Methods: qualitative study with phenomenological approach. Fifteen nurses participated in the study, selected according to an intentional snowball type sample. The data were obtained through semi-structured interviews and the transcribed information was submitted to thematic-category content analysis. Results: from the analysis of the participants' discourse, the following categories and subcategories emerged: lived experiences (negative states; work organization; team cohesion; challenges and norms and guidelines); adopted strategies (individual; team support; familiar and informative) and future expectations (return to normality; adaptation; personal and professional growth; nursing uncertainty and valorization). Conclusion: from the perceptions and experiences of the nurses of their performance in the COVID-19 Pandemic, the negative emotional states, strategies adopted of individual character and future expectations of return to normality are highlighted.